DEVELOPMENT OF TEACHING MATERIALS BASED ON THE RADEC MODEL TO IMPROVE THE HOTS OF GRADE V ELEMENTARY SCHOOL STUDENTS - Hasanatul Fitri; Yanti Fitria; Solfema; Elfia Sukma (Universitas Majalengka, 2023)
Challenges and changes in the 21st century require students to have 4C skills (Critical Thinking, Collaboration, Communication, and Creativity). These 4C skills are closely related to HOTS or higher-order thinking skills. Familiarizing students with HOTS skills in making decisions will be able to act quickly and efficiently compared to students who are less trained in HOTS thinking. These HOTS skills should be loaded into RADEC-based teaching materials. However, its application is still not optimal at the SD level. This study aimed to develop teaching materials based on the RADEC model (Read, Answer, Discuss, Explain and Create) to improve the good high-order thinking skills of fifth-grade elementary school students. The model used in this development research is the 4-D development model. It is a model that defines, designs, develop, and distributes information. Sixty-one fifth-grade students from SDN 35 Payakumbuh, SDN 13 Payakumbuh and SDN 07 Payakumbuh participated in this study. The products developed are tested for validity using validation sheets from material experts, linguists, and media experts. This validation sheet is used to determine the validity of their answers. Material expert validation scored 94% in the